Morphogenesis of the gametophytes of eight Mexican species of Blechnum (Blechnaceae) - Mendoza-Ruiz, Aniceto; Pérez-García, Blanca (Instituto de Ecología, A.C., 2009)
A comparative study of the gametophytes of eight Mexican species of the genus Blechnum (Blechnaceae) is described. Fertile plants for spore collection were obtained at different Mexican localities. The spores were sown in agar enriched with Thompson media and cultured at 22-25 °C, with a light regime of 12 hours. Spores of all species are monolete, ellipsoidal to spheroidal, and non-chlorophyllous. Vittaria-type germination occurred after 6-14 days followed by a 2-6-cell-long filament and Aspidium-type prothallial development. Adult gametophytes are cordiform-spatulate to cordiform-reniform and have wide wings with numerous unicellular marginal and superficial hairs. Sporophytes developed only in B. occidentale and B. polypodioides.